Problems with the Turkish Translations of the Convention for the Protection of Human Rights and Fundamental Rights - (:unkn) unknown (ISTANBUL UNIV, 2021)
This study analyzes Turkish translations of the Convention for Protection of Human Rights and Fundamental Freedoms, the official versions of which are in English and French. Nine different Turkish translations of this document have been identified. The first of these translations was published in the Official Gazette in 1954; this translation, however, is rarely used in practice. The second translation was published on the website of the European Court of Human Rights (ECtHR). This text, which is frequently cited in decisions of high judicial bodies and scholarly literature, contains many grammatical errors and mistranslated concepts. Additionally, the author of this translation is unknown. There are seven other translations that have been completed by various authors; these translations also contain inconsistencies and semantic issues. This study undertakes in-depth analysis of the translations mentioned above. The concluding section of the article proposes a new translation and emphasizes the need for a workshop involving the Constitutional Court and experts from different disciplines. Such a workshop would serve both to internalize the text and to standardize the practice of law.
Keywords: Translation; legal English; European Convention on Human Rights